Academic Senate Minutes 2003-10-16 - Academic Senate:::::::::
Report from the Chair. Report from the President. Agenda and minutes approved. Resolution from the Lecturer's Council regarding Enterprises surplus, second reading, tabled. Report "First Generation, Low Income undergraduate Students" presented by Richard Rodriguez and Elisa Velasquez. Report on Community Solidarity Fund. Report from Provost Ochoa, Chair- Elect, Statewide Senator and APC.